Characterization of Oxytocin Receptor Expression Within Various Neuronal Populations of the Mouse Dorsal Hippocampus - Young, W. Scott; Song, June (Frontiers in Molecular Neuroscience, 2020)
Oxytocin, acting through the oxytocin receptor (Oxtr) in the periphery, is best known for its roles in regulating parturition and lactation. However, it is also now known to possess a number of important social functions within the central nervous system, including social preference, memory and aggression, that vary to different degrees in different species. The Oxtr is found in both excitatory and inhibitory neurons within the brain and research is focusing on how, for example, activation of the receptor in interneurons can enhance the signal-to-noise of neuronal transmission. It is important to understand which neurons in the mouse dorsal hippocampus might be activated during memory formation. Therefore, we examined the colocalization of transcripts in over 5000 neurons for Oxtr with those for 9 different markers often found in interneurons using hairpin chain reaction in situ hybridization on hippocampal sections. Greater than 90% of the Oxtr non-CA2/CA3 pyramidal cell neurons co-express glutamic acid decarboxylase-1 (Gad-1) with progressively decreasing numbers of co-expression with cholecystokinin, somatostatin, parvalbumin, neuronal nitric oxide synthase, the serotonin 3a receptor, the vesicular glutamate transporter 3, calbindin 2 (calretinin), and vasoactive intestinal polypeptide neurons. Distributions were analyzed within hippocampal layers and regions as well. These findings indicate that Oxtr activation will modulate the activity of approximately 30% of the Gad-1 interneurons and the majority of the diverse population of those, mostly, interneuron types specifically examined in the mouse hippocampus.